Neurological impact of HIV/AIDS and substance use alters brain function and structure - Haorah, James; Malaroviyam, Samikkannu; Iyappan, Hemavathi; Samikkannu, Thangavel (Frontiers in Medicine, 2025)
Human immunodeficiency virus (HIV) infection is the cause of acquired immunodeficiency syndrome (AIDS). Combination antiretroviral therapy (cART) has successfully controlled AIDS, but HIV-associated neurocognitive disorders (HANDs) remain prevalent among people with HIV. HIV infection is often associated with substance use, which promotes HIV transmission and viral replication and exacerbates HANDs even in the era of cART. Thus, the comorbid effects of substance use exacerbate the neuropathogenesis of HANDs. Unraveling the mechanism(s) of this comorbid exacerbation at the molecular, cell-type, and brain region levels may provide a better understanding of HAND persistence. This review aims to highlight the comorbid effects of HIV and substance use in specific brain regions and cell types involved in the persistence of HANDs. This review includes an overview of post-translational modifications, alterations in microglia-specific biomarkers, and possible mechanistic pathways that may link epigenomic modifications to functional protein alterations in microglia. The impairment of the microglial proteins that are involved in neural circuit function appears to contribute to the breakdown of cellular communication and neurodegeneration in HANDs. The epigenetic modification of N-terminal acetylation is currently understudied, which is discussed in brief to demonstrate the important role of this epigenetic modification in infected microglia within specific brain regions. The discussion also explores whether combined antiretroviral therapy is effective in preventing HIV infection or substance-use-mediated post-translational modifications and protein alterations in the persistence of neuropathogenesis in HANDs.